If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -5y = -1 Solving 4 + -5y = -1 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -5y = -1 + -4 Combine like terms: 4 + -4 = 0 0 + -5y = -1 + -4 -5y = -1 + -4 Combine like terms: -1 + -4 = -5 -5y = -5 Divide each side by '-5'. y = 1 Simplifying y = 1
| t-5=-12 | | 7d=63 | | -2+n=-13 | | 3+2(1+2n)=-7 | | 6x+5(-4x+15)=-65 | | 8=a+5 | | 9+n=14 | | -6+a=-3 | | t-6=-9 | | 8+b=12 | | 20=-d+15 | | 132=2x+5(x+11) | | -6b=60 | | 11=a+6 | | t+8=-4 | | 8=a+1 | | 4+m=14 | | 7+w=0 | | 4(k+1)=-64 | | a+10=11 | | 2+w=12 | | -5m=-5 | | -12=m-4 | | w/7=4 | | 8y= | | -12=2(-10+a) | | -98=-3x-4(-4x+5) | | 1+t=-1 | | -2d=-24 | | w+2=4 | | k-5=-16 | | 5d=10 |